Surveying the Obstacles to Effective English Communication in Physics Tutorials - Khairiah, Rhea; Wiardy, Achmad; Wahyunengsih (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to describe how English is used to support communication during physics tutorial activities and to analyze the linguistic, psychological, and environmental factors that hinder effective communication among students during English-medium physics tutorials. Methodology: This study used a descriptive survey design involving 50 physics students. Data were collected through a 50-item Likert-scale questionnaire developed based on theoretical frameworks in language learning and science education. All responses were processed using descriptive statistical techniques in Microsoft Excel to identify dominant linguistic, psychological, and environmental communication barriers. Main Findings: The results of the study show that psychological barriers, especially anxiety when speaking, fear of making mistakes, and lack of confidence, are the biggest obstacles in the communication process. In addition, there are also linguistic challenges, such as limited technical vocabulary and difficulty in accurately formulating scientific expressions. Environmental factors, including the speed of delivery and lack of language support, further exacerbate these communication difficulties. Novelty/Originality of this study: This study conducts an in-depth analysis of communication barriers in physics tutorial activities, a context that has been previously under-discussed in the literature. By integrating linguistic, psychological, and environmental perspectives, this study presents new empirical findings that can enrich more inclusive pedagogical practices and support the development of science learning strategies that use English as the medium.